UBE2N as a novel prognostic and therapeutic biomarker of lung adenocarcinoma - Yin, Haofeng; Xue, Yibo; Wang, Chen; Wu, Yanqin; Guo, Yuchen; Li, Chunzhen; Zhang, Yunyan; Yin, Shulei; Zhao, Tiejun (Frontiers in Immunology, 2025)
BackgroundLung adenocarcinoma (LUAD) represents a significant global health burden. The absence of reliable biomarkers and the heterogeneity in treatment responses continue to hinder improvements in patient prognosis. This study aimed to identify novel biomarkers capable of predicting patient outcomes and therapeutic responsiveness, while also assessing their potential as intervention targets for LUAD.MethodsMultiple cohorts from public databases were employed to screen key prognostic genes, followed by external validations. Clinicopathological indicators were integrated to analyze the independent prognostic role of the key gene UBE2N and its association with LUAD progression. Functional enrichment analysis elucidated the biological mechanisms regulated by UBE2N. Differences in immune microenvironment components, immunoregulatory gene expression, and immune functional activities between subgroups stratified by UBE2N expression levels. The role of UBE2N in predicting tumor therapeutic susceptibility was characterized using bioinformatics algorithms combined with publicly available CRISPR screening datasets and immunotherapy cohorts. Immunohistochemistry, cell viability, and apoptosis experiments were conducted to verify the oncogenic effects of UBE2N.ResultsUBE2N was identified as an independent prognostic biomarker for LUAD. Elevated UBE2N expression correlated with poorer patient survival rates and advanced disease stages. Genes associated with UBE2N were significantly enriched in critical cellular processes, including DNA replication, nucleosome assembly, and neutrophil extracellular trap formation. High-UBE2N tumors exhibited enhanced cell cycle, DNA replication, and oxidative phosphorylation activities. Low-UBE2N tumors exhibit elevated proportions of intratumoral NK cells, dendritic cells, effector T cells, and enhanced antigen processing and presentation. UBE2N was a potential promoter of immune evasion and drug resistance, with its high expression suggestive of low responsiveness to cancer immunotherapy and targeted therapies. Three potential UBE2N-inhibiting compounds were identified. Tissue microarrays confirmed UBE2N overexpression in LUAD, correlating with tumor size, while UBE2N knockdown suppressed tumor cell viability and induced apoptosis.ConclusionsUBE2N may serve as a promising prognostic biomarker and therapeutic target for LUAD. Inhibition of UBE2N is expected to suppress LUAD progression and enhance therapeutic efficacy.